The Role of IL-17 During Infections in the Female Reproductive Tract - Bagri, Puja; Anipindi, Varun C.; Kaushic, Charu (Frontiers in Immunology, 2022)
Interleukin-17 (IL-17A) is a cytokine involved in a complex array of both protective and detrimental processes. Although early biological studies focused on the pro-inflammatory function of IL-17 in the context of autoimmune and inflammatory disorders, it has become increasingly evident that the roles of IL-17 are far more nuanced. Recent work has demonstrated that the functions of IL-17 are highly context- and tissue-dependent, and there is a fine balance between the pathogenic and protective functions of IL-17. This is especially evident in mucosal tissues such as the female reproductive tract, where IL-17 has been shown to play an important role in the immune response generated during fungal, bacterial and viral infections associated with protection, but also inflammation. In this review, we discuss the evolving landscape of IL-17 biology within the context of the vaginal mucosa, focusing on key findings that highlight the importance of this cytokine in genital mucosal immunity.